2007
DOI: 10.1074/jbc.m609317200
|View full text |Cite
|
Sign up to set email alerts
|

Aminosulfonate Modulated pH-induced Conformational Changes in Connexin26 Hemichannels

Abstract: Gap junction channels regulate cell-cell communication by passing metabolites, ions, and signaling molecules. Gap junction channel closure in cells by acidification is well documented; however, it is unknown whether acidification affects connexins or modulating proteins or compounds that in turn act on connexins. Protonated aminosulfonates directly inhibit connexin channel activity in an isoform-specific manner as shown in previously published studies. High-resolution atomic force microscopy of force-dissected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 74 publications
2
66
0
Order By: Relevance
“…Prior to SMFS, membranes containing densely packed SteT were located by contact mode AFM imaging. If necessary, the AFM stylus was used as a nanoscalpel to remove aggregates or the upper layer of the vesicles (47,48). An unperturbed area of the membrane patch was selected, and the AFM stylus was pushed onto the membrane at a force of ϳ750 pN for 0.5-1.0 s to promote unspecific attachment of the SteT polypeptide to the AFM stylus.…”
Section: Methodsmentioning
confidence: 99%
“…Prior to SMFS, membranes containing densely packed SteT were located by contact mode AFM imaging. If necessary, the AFM stylus was used as a nanoscalpel to remove aggregates or the upper layer of the vesicles (47,48). An unperturbed area of the membrane patch was selected, and the AFM stylus was pushed onto the membrane at a force of ϳ750 pN for 0.5-1.0 s to promote unspecific attachment of the SteT polypeptide to the AFM stylus.…”
Section: Methodsmentioning
confidence: 99%
“…Because biomolecules are 'alive' under these native conditions, AFM has been successfully used to observe single proteins at work; for reviews, see Engel et al (1999) and Engel and Müller (2000). One of the most exciting examples in the literature for the direct visualization of conformational changes is the pH and Ca 2q -dependent opening and closing of the gap junction channel connexin26 Yu et al, 2007). Because of these unique capabilities, AFM is currently being used as a complementary technique to XRC and electron microscopy.…”
Section: Atomic Force Microscopy (Afm)mentioning
confidence: 99%
“…KirVac3.1 is one member of a family of transmembrane potassium channels, and gating of Kir channels is spontaneous but modulated by intracellular molecules such as lipids (PIP2), G-proteins, nucleotides, and ions (H + , Ca 2+ , Mg 2+ ). Yu et al (2007) demonstrated that pH-induced conformational changes in connexin 26 hemichannels were modulated by aminosulfonate. They removed the upper layer of the gap junction channel by repetitive scanning AFM tip with loading of strong force.…”
Section: Imaging Of Membrane Channelsmentioning
confidence: 99%
“…Efforts to observe the ultra-structures of cells using AFM have gradually increased since its invention Muller and Engel, 1999;Kreplak et al, 2007;Jaroslawski et al, 2007;Yu et al, 2007). Early studies of cells with AFM were focused on topological observation by high-reso-lution imaging.…”
Section: Applications Of Afm To Imaging Of Membrane Proteinsmentioning
confidence: 99%
See 1 more Smart Citation